2014
DOI: 10.5539/jfr.v4n2p68
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drying Methods and Ultrasonication in Improving the Antioxidant Activity and Total Phenolic Content of Apple Pomace Powder

Abstract: Although extrusion is a promising process to develop ready to eat cereals and snacks, thermal treatment to raw material during extrusion results in degradation of phenolic compounds. Therefore, an approach was made to enhance the total phenolic content (TPC) and antioxidant activity (AA) of apple pomace (AP) prior to extrusion process. In this study, AP powder was naturally fermented (F) for 12 h and then was subjected to ultrasonication (U) at various conditions [25, 37, and 50 µm ultrasonication amplitude (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
(23 reference statements)
1
13
0
Order By: Relevance
“…Candrawinata et al . (), and Lohani & Muthukumarappan () also reported high correlation between TPC and AA of AP.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Candrawinata et al . (), and Lohani & Muthukumarappan () also reported high correlation between TPC and AA of AP.…”
Section: Resultsmentioning
confidence: 85%
“…Our comprehensive literature review revealed that in the past few years, ultrasound assisted extraction of phenolic compounds from AP has been extensively investigated (Grigoras et al, 2013;Candrawinata et al, 2014) but application of the fermentation followed by ultrasonication to enhance phenolics as well as functional properties in AP is limited. Even though Lohani & Muthukumarappan (2015) found a significant (P < 0.05) increase in TPC and AA of AP after fermentation followed by the ultrasonication and microwave drying, more levels of the fermentation time (FT), ultrasonication parameters (intensity, time) and microwave power (MWP) are needed to be explored. Therefore, keeping in view above facts, the objective of this study was to investigate the influence of sequential treatments of fermentation and ultrasonication followed by microwave drying on TPC and AA of AP.…”
Section: Introductionmentioning
confidence: 99%
“…So, considering the solvents, the present outputs fitted to Arunachalam et al (2011) Candrawinata et al (2014) found that an increasing temperature permitted an increasing extraction of total phenols, thus an increasing antioxidant activity. As aside results, Lohani and Muthukumarappan (2015) proved that the interaction effects between two independent variables mainly reduce the derived result. For instance, looking at the drying method (DM) and ultrasonication amplitude (UA) effects on apple pomace separately, they reported 6788.3334 and 1876.8693, respectively; while the interaction (DM*UA) leaded to 1594.1769 µmol TE/g.…”
Section: Antioxidant Activity (Abts*+)mentioning
confidence: 73%
“…In addition, Lohani and Muthukumarappan (2015) indicated that the phenolic compounds can be liberated by heat treatment, and moreover, Jeong et al (2004) came to the conclusion that phenols should have different bound status along with plant species. In accordance with Lohani and Muthukumarappan (2015), compare to raw material, dried products exhibit higher phenolic compound extracts. For example, the fresh exhibited 3.125 versus 3.5 mg GAE/g for the dried apple pomace at 50 o C. Furthermore, they found that, when the product is fermented then dried, it exhibits higher total phenols extracts.…”
Section: Total Phenolsmentioning
confidence: 99%
See 1 more Smart Citation